Recent advances in Bcr‐Abl tyrosine kinase inhibitors for overriding T315I mutation. (29th October 2020) - Liu, Juan; Zhang, Yuan; Huang, Honglin; Lei, Xiaoyong; Tang, Guotao; Cao, Xuan; Peng, Junmei
Abstract: BCR‐ABL is a gene produced by the fusion of the bcr gene and the c‐abl proto‐oncogene and is considered to be the main cause of chronic myelogenous leukemia (CML) production. Therefore, the development of selective Bcr‐Abl kinase inhibitors is an attractive strategy for the treatment of CML. However, in the treatment of CML with a Bcr‐Abl kinase inhibitor, the T315I gatekeeper mutant disrupts the important contact interaction between the inhibitor and the enzyme, resistant to the first‐ and second‐generation drugs currently approved, such as imatinib, bosutinib, nilotinib, and dasatinib. In order to overcome this special resistance, several different strategies have been explored, and many molecules have been studied to effectively inhibit Bcr‐Abl T315I. Some of these molecules are still under development, and some are being studied preclinically, and still others are in clinical research. Herein, this review reports some of the major examples of third‐generation Bcr‐Abl inhibitors against the T315I mutation. Abstract : In this paper, some of the major examples of Bcr‐Abl inhibitors against the T315I mutation are reviewed.